Swiss Survey on current practices and opinions on clinical constellations triggering the search for PNH clones - Rovó, Alicia; Gavillet, Mathilde; Drexler, Beatrice; Keller, Peter; Schneider, Jenny Sarah; Colucci, Giuseppe; Beauverd, Yan; Dorland, Hendrika Anette van; Pollak, Matthias; Schmidt, Adrian; De Gottardi, Andrea; Bissig, Marina; et al. (Frontiers in Medicine, 2023)
This national survey investigates the current practice in Switzerland by collecting participants' opinions on Paroxysmal Nocturnal Hemoglobinuria (PNH) clone assessment and clinical practice. AIMS: To investigate clinical indications prompting PNH clones' assessment and physician's accessibility to flow-cytometry facility. To understand clinical attitudes for the follow-up (FU) of patients harboring PNH clones.METHODS: The survey includes 16 multiple-choice questions related to PNH and targets physicians with a definite level of experience in the topic using two-screener questions. Opinion on clinical management was collected using hypothetical clinical situations. Each participant could select the option to be contacted to further discuss the survey results. This was an online survey, 264 physicians were contacted via email once a week for 5 weeks, from September 2020. RESULTS: In total, 64 physicians (24.2%) from 23 institutions participated (81.3% hematologists, 67.2% from university hospitals). All had access to flow-cytometry for PNH clone testing, 76.6% in their own institution. The main reasons to assess for PNH clones were unexplained thrombosis and/or hemolysis, and/or aplastic anemia (AA). Patients in FU for PNH clones were more likely to be aplastic anemia (AA) and symptomatic PNH. 61% of the participants investigate PNH clones repetitively during FU in AA/ myelodysplastic syndromes patients, even when there was no PNH clone found at diagnosis, and 75% tested at least once a year during FU. Opinions related to clinical management were scattered. CONCLUSIONS: The need to adhere to guidelines for the assessment, interpretation and reporting of PNH clones, emerges as the most important finding, as well as consensus for the management of less well-defined clinical situations. Even though there are several international guidelines, clear information addressing specific topics like the type of anticoagulant to use and its duration, as well as the indication for treatment with complement inhibitors in some borderline situations are needed. The analysis and the discussion of this survey provide the basis to understand unmet needs of PNH clone assessment and clinical practice in Switzerland.